Investor perceptions of board performance: Evidence from uncontested director elections - Fischer, Paul E.; Gramlich, Jeffrey D.; Miller, Brian P.; White, Hal D. (Journal of Accounting and Economics, 2009)
This paper provides evidence that uncontested director elections provide informative polls of investor perceptions regarding board performance. We find that higher (lower) vote approval is associated with lower (higher) stock price reactions to subsequent announcements of management turnovers. In addition, firms with low vote approval are more likely to experience CEO turnover, greater board turnover, lower CEO compensation, fewer and better-received acquisitions, and more and better-received divestitures in the future. These findings hold after controlling for other variables reflecting or determining investor perceptions, suggesting that elections not only inform as a summary statistic, but incrementally inform as well.